Study on the effect of fissures in expansive soils on permeability and engineering effects of canal slopes - Bin LI; Yuanjiang JU; Bo SONG; Kaidi ZHANG; Jifeng HAO; Zhimin ZHANG (Zhongguo dizhi zaihai yu fangzhi xuebao)
Expansive soils represent a special type of unsaturated soil and constitute a major component of the soil structure in the initial canal section of the middle route of the South-to-North Water Transfer Project(MR-SNWTP). Compared to typical cohesive soils, expansive soils exhibit fissures that can impact their permeability, subsequently influencing the drainage efficiency of expansive soil slopes. To investigate the relationship between permeability of expansive soils, fissures, and moisture content, percolation tests were carried out on unsaturated expansive soils in the relevant region using a self-made permeability apparatus. The experimental results indicate that the permeability coefficient of soil samples with different initial conditions decreases gradually during percolation in a saturated environment. At the same initial water content, the greater the fracture ratios of the soil sample, the greater the permeability coefficient and the longer it takes for the permeability coefficient to reach a steady state. Under equal initial moisture content, greater fissure rates of soil samples result in higher permeability coefficients, and the time required for the permeability coefficient to stabilize increases. Under the same initial fissure rate, soil samples with lower initial moisture content exhibit lower permeability but higher matric suction; however, rapid expansion due to water absorption leads deteriorating permeability. By analyzing the changes in soil permeability coefficients during the transition from different initial conditions to a saturated state, it is observed that the drainage effectiveness of canal slope drainage facilities is most significant within 2 hours of the start of the seepage, remains noticeable within 8 hours, and becomes limited after 8 hours.